Hotel on Pallas fell - Maunula, Raisa (2010)
This master's thesis is based on law proposal allowing more building in Pallas-Ylläs national park. The maximum building area, building height and number of beds for extension of the old hotel is determined by the law. In this thesis, the above mentioned restrictions have been taken under consideration, and the aim has been finding solution that suits the site. With its 400 000 visitors a year Pallas-Yllästunturi national park is one of the most visited in Finland. The beautiful scenery has attracted visitors already in the 18 th century. The first ski tourist arrived in the 30's and first hotel on the area was built in 1938. It was a true portrait of the era: a white plastered cube up on the fell with its occupant's - modern cit dwellers. Architect Väinö Vähäkallio included also some new ecological innovations on the building such as adjustable heating system based on the number of patrons. After the war in 1944, German soldiers exploded the whole building. The new hotel designed by Jouko Ylihannu was built in 1948. Traditional log structured building was more appropriate in the atmosphere of after war Finland. Still it managed to be cutting edge with its triple glazed windows. The interior design was praised, also abroad. This Masters thesis proposes a new sustainable hotel adjoining the soon to be listed protected old hotel. Architecturally poor previous extensions would be demolished. Sustainability in this building is based on wood construction, minimizing heat loss with passive house building standards and optimizing daylight. Photovoltaic panels capture energy and materials are environmentally friendly. Energy saving was also considered in the room designs. New hotel has 100 beds and the old building 36. The new rooms are flexible to please different user groups. Number of beds can be adjusted up to 200 pieces. The sustainable hotel offers an alternative for the visitors standing out from the other for travel centres in Lapland. Gross floor area of the new building is 6104m 2 and the area of the old ...